1998
DOI: 10.1021/bp970119k
|View full text |Cite
|
Sign up to set email alerts
|

Steam‐Sterilizable, Fluorescence Lifetime‐Based Sensing Film for Dissolved Carbon Dioxide

Abstract: An autoclavable sensing film was developed for monitoring dissolved CO2. The sensing film, based on fluorescence resonance energy transfer (FRET), consisted of a fluorescent donor, an acceptor, and a quaternary ammonium hydroxide, which were doped in a two-component silicone film. As no aqueous solution was used in the sensing film matrix, the sensing film was unaffected by osmotic pressure. Fluorescence lifetime was selected as the sensing parameter, and measured in frequency domain using phase fluorometry. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 23 publications
(24 reference statements)
1
11
0
Order By: Relevance
“…The reason for the observed loss of signal may be the effect of additional curing of the polymer support matrix that increases its opacity. These results are consistent with previous findings demonstrating that fluorescent-based dissolved gas sensors can be autoclaved (6,10). should be linear for dynamic quenching in a homogeneous matrix.…”
Section: Resultssupporting
confidence: 93%
“…The reason for the observed loss of signal may be the effect of additional curing of the polymer support matrix that increases its opacity. These results are consistent with previous findings demonstrating that fluorescent-based dissolved gas sensors can be autoclaved (6,10). should be linear for dynamic quenching in a homogeneous matrix.…”
Section: Resultssupporting
confidence: 93%
“…The rather elegant work of Chang et al 50 appears to lend support to this proposal, in their study of steam sterilisable fluorescence lifetime-based sensing films for carbon dioxide. Thus, by comparing films containing the same quantity but different quaternary ammonium hydroxides, these workers found that the order of sensor film stability (with number of β-hydrogens in parenthesis) was: TOAH (8) < CTAH (2) < TMAH (0).…”
Section: Dry Optical Sensors For Carbon Dioxidementioning
confidence: 88%
“…A number of studies, carried out using dry and wet luminescent optical sensors for carbon dioxide, have illustrated the efficacy of these indicators for the detection and measurement of carbon dioxide in: blood 24 , food packages 69 , bioreactors 26,50 and seawater 30 . However, despite this success and promise, these sensors have been slow to take off as commercial products and the detection and analysis of carbon dioxide is still dominated by the Severinghaus electrode (dissolved work) and infrared spectroscopy (gaseous work).…”
Section: Applications and Practical Systemsmentioning
confidence: 99%
“…With the invention of disposable noninvasive sensors, this situation might be changed quickly in the future. The disposable noninvasive sensors for pH, DO, and CO 2 used in this study were developed by the authors' laboratory 10–20. All patches share a similar multilayer structure with a sensitive dye immobilized in the responsive layer of the sensing patch.…”
Section: Introductionmentioning
confidence: 99%